Il carteggio fra Enrico Betti e Quintino Sella 1861-1883 - The correspondence between Enrico Betti and Quintino Sella 1861-1883 - Clara Silvia Roero (Rivista di Storia dell'Università di Torino, 2024)
This paper focus on the relationships between the mathematician Enrico Betti (1823-1892) and the statesman and scientist Quintino Sella (1827-1884) in the crucial period of Italy’s unification. They shared the same cosmopolitan conception of science that they embraced during their yourneys abroad. Their aims were the promotion of Italian science to the highest degree of development in Europe, the creation of a national scientific community, the establishment of public schools to improve the cultural preparation of the new generations, the organization of scholarships and prizers to encourage research, the foundations of specialized periodicals and the proceedings of scientific societies.